Monetary Policy during Financial Crisis: A Comparative Analysis - Snæfríður Baldvinsdóttir 1968- (2011)
The question of how countries should respond to financial crisis is a much debated issue in economics; in particular, the role of high interest rates in stabilizing the exchange rate. Normally exchange rate depreciation leads to increased exports and thus greater demand for the local currency. On the other hand, large depreciation in an open economy can result in corporate bankruptcies, in particular when banks or corporations have major foreign currency obligations, leading to decreased demand for the currency and thus further depreciation. Large depreciations in crises countries thus often call for firmer monetary policy in order to reverse the trend of an overly depreciated currency and to stabilize the exchange rate. This raises questions on the appropriate monetary policy choices. Does tighter monetary policy strengthen the currency? What is the macroeconomic cost of high interest rates? What is the trade-off between appreciation and a weaker economy? Those questons do not lead to one-sided or clear cut answers. In fact, the answers seem to depend on the circumstances. The objective of this paper is to examine those circumstances for three different countries, Thailand, Brazil and Iceland. The paper will examine the relationship between monetary policy and currency stabilization during crisis and in particular, the two opposing views regarding tight monetary policy’s impact on the exchange rate. It will then identify the important factors affecting the objective of nominal appreciation/stabilization, and evaluate their importance for the three crisis cases – Thailand, Brazil, Iceland. Finally it will question the desirability of tight monetary policy in the case of Iceland in terms of cost and benefit trade-off.